2016
DOI: 10.1080/09205063.2016.1170415
|View full text |Cite
|
Sign up to set email alerts
|

Influence of mechanical properties of alginate-based substrates on the performance of Schwann cells in culture

Abstract: In tissue engineering, artificial tissue scaffolds containing living cells have been studied for tissue repair and regeneration. Notably, the performance of these encapsulated-in-scaffolds cells in terms of cell viability, proliferation, and expression of function during and after the scaffold fabrication process, has not been well documented because of the influence of mechanical, chemical, and physical properties of the scaffold substrate materials. This paper presents our study on the influence of mechanica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 43 publications
4
56
0
Order By: Relevance
“…With respect to basic research, in a work by Ning et al [56], the flow behavior of alginate solutions containing living cells was studied. Rheological properties of alginate–Schwann cell, alginate–fibroblast cell, and alginate–skeletal muscle cell suspensions during shearing in the printing process were analyzed, confirming that the flow behavior effects on cells are critical for their viability and proliferation: in addition to temperature and the concentration of the biomaterial, the cell density affects the flow behavior of cell suspensions too.…”
Section: The Use Of Alginate In Three-dimensional (3d) Bioprintingmentioning
confidence: 99%
“…With respect to basic research, in a work by Ning et al [56], the flow behavior of alginate solutions containing living cells was studied. Rheological properties of alginate–Schwann cell, alginate–fibroblast cell, and alginate–skeletal muscle cell suspensions during shearing in the printing process were analyzed, confirming that the flow behavior effects on cells are critical for their viability and proliferation: in addition to temperature and the concentration of the biomaterial, the cell density affects the flow behavior of cell suspensions too.…”
Section: The Use Of Alginate In Three-dimensional (3d) Bioprintingmentioning
confidence: 99%
“…In some tissue engineering applications, such as peripheral nerve (Ning et al, 2016), bone (Naghieh et al, 2016b), and articular cartilage (You et al, 2016b) regeneration, scaffolds undergo compressive force exerted by over-and underlying tissues in one direction. In such cases, the compressive elastic modulus is important in one direction while the scaffold mechanical behavior in other directions might be different; indeed, bioprinted scaffolds are not isotropic (Olubamiji et al, 2016).…”
Section: Figure 2 the Model Developed To Represent The Structure Of mentioning
confidence: 99%
“…Analogously, using an advanced bioreactor system, the impact of tensile forces on cell differentiation within a 3D collagen construct was demonstrated when uniaxial static or dynamic stretch was utilized on mouse ESC‐embedded matrices . When Schwann cells were encapsulated within alginate‐based hydrogels using varying alginate concentrations, the mechanical properties of the materials exerted an important effect on the performance of these cells . Interestingly, recent evidence demonstrated that 3D mechanical stimulation could replace chemical pre‐stimulation ( e.g ., TGF‐β1) to yield smooth muscle cells from adipose tissue‐derived stromal cells, offering a novel approach to engineering bioartificial arteries in vascular tissue engineering .…”
Section: Engineering a 3d Home For Cell Accommodationmentioning
confidence: 99%